Strengthening Women-Led Village Savings Associations to Provide Loans to Women - Kilanga, Lucyphine; Kakwasha, Keagan; Kitogo, Lawrence; Simbila, Deogratius; Muzungaire, Lizzy; Chileya, Agness; Lukanga, Editrudith; Mudege, Netsayi (WorldFish, 2024)
Following the completion of the study, WorldFish, the Tanzania Women Fish Workers Association (TAWFA), which is the Tanzanian chapter of the African Women Fish Processors and Traders Network (AWFISHNET), and the Environmental Management and Economic Development Organization (EMEDO) partnered to disseminate and validate research findings and identify leverage points to transform gender norms and make women economically resilient to the impacts of climate change in the fisheries value chain.